Single Si submicron wire photodetector fabricated by simple wet etching process - Lee, Dong-Ki; Ko, Hyungduk; Cho, Younghak (ELSEVIER, 2015)
In this paper, we report on an oxidized single Si submicron wire photodetector with a metal-semiconductor-metal (MSM) structure. The single Si submicron wire was successfully fabricated using a simple and cost-effective wet etching process. The single Si submicron wire photodetector with SiO2 layer achieved responsivity of 1.84 A/W and external quantum efficiency (EQE) of 6.23 x 102% with illumination of 365 nm. Furthermore, rapid and stable ON/OFF switching was achieved and reproducible by the oxidation of the Si surface. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: NANOWIRE; HETEROJUNCTION; ABSORPTION